'A More Lively Feeling': The Correspondence and Integration of Mystical and Spatial Dynamics in John Woolman's Travels. Issue 1 (March 2015) - Kershner, Jon R.
Abstract : John Woolman went on more than 30 ministry journeys, averaging one month traveling a year. Woolman's Journal demonstrates that these ministry travels were important to his spiritual and ethical formation. Woolman's understanding of divine revelation and ethical discernment developed in the space for reflection provided by travel and in the affordances of the landscape he passed through. As Woolman continued to travel, the theological and social integration of his ministry deepened. This article explicates the relationship between the physical activity of itinerant ministry and the formative effect it had on Woolman's social and theological convictions. Additionally, this research argues that Woolman used the aesthetics of travel as an act of prophetic embodiment intended to challenge those he encountered.